Carbonate reservoir characterization : a geologic-engineering analysis. - Chilingar, George V., 1929-; Mazzullo, S. J.; Rieke, Herman H.; Dominguez, G. C.; Samaniego, V. F.; ScienceDirect eBooks (Amsterdam ; Oxford : Elsevier., 1996)
This second volume on carbonate reservoirs completes the two-volume treatise on this important topic for petroleum engineers and geologists. Together, the volumes form a complete, modern reference to the properties and production behaviour of carbonate petroleum reservoirs. The book contains valuable glossaries to geologic and petroleum engineering terms providing exact definitions for writers and speakers. Lecturers will find a useful appendix devoted to questions and problems that can be used for teaching assignments as well as a guide for lecture development. In addition, there is a chapter devoted to core analysis of carbonate rocks which is ideal for laboratory instruction. Managers and production engineers will find a review of the latest laboratory technology for carbonate formation evaluation in the chapter on core analysis. The modern classification of carbonate rocks is presented with petroleum production performance and overall characterization using seismic and well test analyses. Separate chapters are devoted to the important naturally fractured and chalk reservoirs. Throughout the book, the emphasis is on formation evaluation and performance. This two-volume work brings together the wide variety of approaches to the study of carbonate reservoirs and will therefore be of value to managers, engineers, geologists and lecturers.
Introduction -- Seismic expression of carbonate reservoir systems -- Core analysis and its application in reservoir characterization -- Formation evaluation -- Performance and classification of carbonate reservoirs -- Well test analysis in carbonate reservoirs -- Naturally-fractured carbonate reservoirs -- Chalk Reservoirs -- Hydrocarbon reservoirs in karsted carbonate rocks -- Factors affecting oil recovery from carbonate reservoirs and prediction of recovery -- Appendixes -- Glossary of selected geologic terms -- Petroleum engineering glossary -- Fundamentals of surface and capillary forces -- Sample questions and problems.
Print version record.
Elsevier
Keywords: Carbonate reservoirs; Oil reservoir engineering; TECHNOLOGY & ENGINEERING -- Petroleum; Carbonate reservoirs; Oil reservoir engineering; Electronic books